Mortality risk is increased in chronotropic incompetent device carriers with acute heart failure. (3rd October 2022) - Huttelmaier, M; Muensterer, S; Morbach, C; Sahiti, F; Scholz, N; Albert, J; Angermann, C; Ertl, G; Frantz, S; Stoerk, S; Fischer, T
Abstract: Introduction: In heart failure (HF), chronotropic incompetence is a major factor limiting cardiac output and exercise capacity. In patients carrying cardiac implantable electronic devices (CIED), accelerometer-based rate adaption (R-mode) counterbalances chronotropic incompetence during physical activity but fails to modulate heart rate under circumstances of high metabolic demand. Purpose: We hypothesized that an activated R-mode, a surrogate of chronotropic incompetence, indicates worse prognosis during and after episodes of acutely decompensated HF (AHF). Methods: We analysed 632 patients enrolled between 01/2014 and 02/2018 in an ongoing registry that phenotypes and follows patients admitted for AHF. We compared CIED carriers with activated R-mode (CIED-R; n=37, 16% women) with CIED carriers not in R-mode (CIED-0; n=64, 23% women) and patients without CIEDs (no-CIED; n=511, 43% women). Information on survival status was collected up to 12 months after discharge from index hospitalisation (IH). Uni- and multivariable Cox proportional hazard regression was used to identify predictors of 12-month mortality risk. Results: Mean age of the study sample was 74 (11) years, 39% were women, median LVEF on admission was 51 (quartiles 32, 59) % and de novo HF was detected in 20% of all patients. Median length of IH was 10 (7, 14) days. In-hospital mortality was similar across groups, but 12-month mortality risk was affected by chronotropic incompetence as indicated by R-mode activation: age- and sex-associated hazard ratio (HR) for CIED-R was 2.61 (95% CI 1.59–4.29, p<0.001) compared to group no-CIED, and 2.44 (95% CI 1.25–4.74, p=0.009) compared to group CIED-0. Amongst univariable predictors of mortality risk, strong associations were found for NT-proBNP levels (p<0.001), Charlson comorbidity index (p=0.001), and de novo HF (p=0.003). These effects persisted after multivariable adjustment for comorbidity burden. Within CIED-R, mortality risk was similar in patients with pacemakers vs. ICDs (HR 1.20, 95% CI 0.49–2.95) and in subgroups with LVEF <50% vs. ≥50% (HR 1.10, 95% CI 0.79–1.53). Mean heart rate on admission was lower in CIED-R vs. CIED-0 or no-CIED (70 bpm vs. 80 bpm or 82 bpm; both p<0.001). Heart rate on admission had no impact on frequency of in-hospital worsenings or death. However, we found a 36% increase in mortality risk per tertile of heart rate at discharge (HR 1.36, 95% CI 1.10–1.69, p=0.004) after exclusion of patients with an activated R-mode. Conclusion: In AHF, R-mode stimulation was associated with an increased 12-month mortality risk, independent of LVEF, type of CIED, burden of comorbidities and type of presentation. Further, increased resting heart rate at discharge predicted 12-month mortality risk only in patients without an activated R-mode. Our findings suggest that chronotropic incompetence per se worsens outcome in AHF and may not be adequately treated through accelerometer-based R-mode stimulation. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Comprehensive Heart Failure Centre (CHFC) Würzburg is funded by the Federal Ministry of Education and Research, Integrated Research and Treatment Centre "Prevention of Heart Failure and its Complications".